THE PRICE OF MERCY: COMMENT TO THE PAPER "PREVENTION OF BETA-THALASSEMIA IN NORTHERN ISRAEL - A COST-BENEFIT ANALYSIS” BY KOREN ET AL - Eliezer Rachmilewitz (Mediterranean Journal of Hematology and Infectious Diseases)
COMMENT TO THE PAPER "PREVENTION OF BETA-THALASSEMIA IN NORTHERN ISRAEL - A COST-BENEFIT ANALYSIS” BY KOREN ET AL